Protected Culture for Vegetable and Small Fruit Crops: The Soilless Trench System - Bielinski M. Santos; Teresa P. Salame-Donoso (EDIS)
Vegetable and small fruit crop production under protective structures, such as greenhouses, high tunnels, and shade houses, often requires using soilless media to mitigate the impact of soilborne diseases, nematodes, and weeds, and it helps with management of fertilization and irrigation. Regardless of the nature and property of the media, they need to be held in containers to avoid direct contact with the soil or to elevate plants above the ground. An alternative to purchasing containers is building a soilless trench system for production of certain vegetables and small fruit crops. This 3-page fact sheet was written by Bielinski M. Santos and Teresa P. Salame-Donoso, and published by the UF Department of Horticultural Sciences, August 2012.